Analysis of The Relationship of Land Transportation With GRDP in Wholesale and Retail Trade Sector, Car and Motorcycle Reparation - Raditya, Rizky Putra; Setiawan, M Ikhsan; Durrotun, Ronny; Bahaswan, Rizal; Prawito, Adi; Heka Ardana, Putu Doddy; Sutapa, I Ketut; Irwansyah, Defi (International Journal of Engineering, Science and Information Technology, 2024)
Transportation Land transportation influences national economic growth. Due to the existence of land transportation modes, the national economy can continue to grow from year to year. This study analyzed the variable relationship between land transportation through road length data, road condition data, and GRDP in the wholesale and retail trade sectors. The results of this study show that good national road conditions have a very low positive correlation (0.079). And has an insignificant relationship to GRDP (0.665 0.05). National road conditions have a shallow level of positive correlation (0.074). And has a negligible relationship to GRDP (0.679 0.05). Damaged national road conditions have a superficial negative correlation (-0.040). And has an insignificant relationship to GRDP (0.823 0.05). National road conditions severely damaged did not pass the requirements test, normality test results (0.024 0.05). Provincial road conditions are good, with a positive correlation (0.681). And has a significant relationship to GRDP (0.00 0.05). Medium local roads have a good level of positive correlation (0.586). And has a substantial relationship to GRDP (0.00 0.05). The condition of damaged provincial roads has a low negative correlation (-0.103). It has an insignificant relationship to GRDP (0.563 0.05). The condition of the badly damaged national road does not pass the requirements test, the normality test (0.024 0.05). Moderate district/city road conditions have an average positive correlation (0.356). And has a significant relationship to GRDP (0.039 0.05). The condition of district/city roads is damaged and has a shallow correlation level of (0.105). It has an insignificant relationship with GRDP (0.555 0.05). The condition of district/city roads is badly damaged and has a shallow correlation level of (0.105). It has an insignificant relationship with GRDP (0.555 0.05). The condition of district/city roads is damaged and has a shallow correlation level of (0.105). It has an insignificant relationship with GRDP (0.555 0.05). The condition of district/city roads is badly damaged and has a shallow correlation level of (0.105). It has an insignificant relationship with GRDP (0.555 0.05). The condition of district/city roads is damaged and has a shallow correlation level of (0.105). It has an insignificant relationship with GRDP (0.555 0.05). The condition of district/city roads is badly damaged and has a shallow correlation level of (0.105). It has an insignificant relationship with GRDP (0.555 0.05).